Discovering the Appalachian Trail : a guide to the trail's greatest hikes - Niven, Joshua; Niven, Amber Adams (Falcon, 2022)
"Discovering the Appalachian Trail has something for everyone who wants a connection with the nation's longest marked footpath at approximately 2,181 miles"--